Internal Structure of Thermoresponsive Physically Crosslinked Nanogel of Poly[N-(2-hydroxypropyl)methacrylamide]-Block-Poly[N-(2,2-difluoroethyl)acrylamide], Prominent 19F MRI Tracer - Babuka, David; Kolouchova, Kristyna; Groborz, Ondrej; Tosner, Zdenek; Zhigunov, Alexander; Stepanek, Petr; Hruby, Martin (Nanomaterials (Basel, Switzerland), 2020)
Fluorine-19 MRI is a promising noninvasive diagnostic method. However, the absence of a nontoxic fluorine-19 MRI tracer that does not suffer from poor biodistribution as a result of its strong fluorophilicity is a constant hurdle in the widespread applicability of this otherwise versatile diagnostic technique. The poly[N-(2-hydroxypropyl)methacrylamide]-block-poly[N-(2,2-difluoroethyl)acrylamide] thermoresponsive copolymer was proposed as an alternative fluorine-19 MRI tracer capable of overcoming such shortcomings. In this paper, the internal structure of self-assembled particles of this copolymer was investigated by various methods including 1D and 2D NMR, dynamic light scattering (DLS), small-angle X-ray scattering (SAXS) and small-angle neutron scattering (SANS). The elucidated structure appears to be that of a nanogel with greatly swollen hydrophilic chains and tightly packed thermoresponsive chains forming a network within the nanogel particles, which become more hydrophobic with increasing temperature. Its capacity to provide a measurable fluorine-19 NMR signal in its aggregated state at human body temperature was also investigated and confirmed. This capacity stems from the different fluorine-19 nuclei relaxation properties compared to those of hydrogen-1 nuclei.
Keywords: magnetic resonance imaging; fluorine-19; PDFEA; diblock copolymer; PHPMA; self-assembly